Suppose that a , b , c ∈ R + , such that a lo g 3 7 = 2 7 , b lo g 7 1 1 = 4 9 , and c lo g 1 1 2 5 = 1 1 . Find a ( lo g 3 7 ) 2 + b ( lo g 7 1 1 ) 2 + c ( lo g 1 1 2 5 ) 2 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
We know from the first three equations that lo g a 2 7 = lo g 3 7 , lo g b 4 9 = lo g 7 1 1 , and lo g c 1 1 = lo g 1 1 2 5 . Substituting, we find
a ( lo g a 2 7 ) ( lo g 3 7 ) + b ( lo g b 4 9 ) ( lo g 7 1 1 ) + c ( lo g c 1 1 ) ( lo g 1 1 2 5 ) .
We know that x lo g x y = y , so we find
2 7 lo g 3 7 + 4 9 lo g 7 1 1 + 1 1 lo g 1 1 2 5
( 3 lo g 3 7 ) 3 + ( 7 lo g 7 1 1 ) 2 + ( 1 1 lo g 1 1 2 5 ) 1 / 2 .
The 3 and the lo g 3 7 cancel out to make 7 , and we can do this for the other two terms. We obtain
7 3 + 1 1 2 + 2 5 1 / 2
= 3 4 3 + 1 2 1 + 5 = 4 6 9 .